2023
DOI: 10.3390/children10020279
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Well-Being in Children and Adolescents during the COVID-19 Pandemic: A Systematic Review

Abstract: Concerns have been raised about the loneliness and well-being of children and adolescents during the COVID-19 pandemic. The extent to which the ongoing pandemic has impacted loneliness and the association between loneliness and well-being is unclear. Therefore, a systematic review of empirical studies on the COVID-19 pandemic was conducted to examine the (1) prevalence of loneliness in children and adolescents, (2) associations between loneliness and indicators of well-being, and (3) moderators of these associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 77 publications
3
20
0
Order By: Relevance
“…Social isolation and quarantine orders have been associated with a 4-fold increased risk in stress-related symptoms among children . Numerous etiological factors for psychopathology also appeared or were exacerbated during the pandemic, including increased screen time, closures and disruptions related to schooling, cancellation of extracurricular activities, increased loneliness, decreased physical activity, and lack of access to school mental health supports . Commensurate with these risk factors were considerable changes to the family milieu, which can have spillover effects on child and adolescent well-being, such as increases in parent depression and anxiety symptoms, family violence, job loss, and alcohol consumption .…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation and quarantine orders have been associated with a 4-fold increased risk in stress-related symptoms among children . Numerous etiological factors for psychopathology also appeared or were exacerbated during the pandemic, including increased screen time, closures and disruptions related to schooling, cancellation of extracurricular activities, increased loneliness, decreased physical activity, and lack of access to school mental health supports . Commensurate with these risk factors were considerable changes to the family milieu, which can have spillover effects on child and adolescent well-being, such as increases in parent depression and anxiety symptoms, family violence, job loss, and alcohol consumption .…”
Section: Introductionmentioning
confidence: 99%
“…Another study (Sprang & Silman, 2013), which was unrelated to the COVID‐19 pandemic, reported that when young people were quarantined and isolated after health‐related disasters, there was an increased risk of developing post‐traumatic stress disorder and anxiety. During the COVID‐19 pandemic, a review (Farrell et al, 2023) observed a significant association between high levels of loneliness and worse well‐being, including symptoms of depression, anxiety, gaming addiction and sleeping problems (Farrell et al, 2023). These conditions, if installed since childhood, can cause several problems related to cognitive, affective and behavioural development.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatives that could be explored include offering the intervention within the context of university‐community partnerships or partnering with afterschool organizations (e.g., Boys and Girls Clubs of America) so that universities or organizations could provide needed supports. All possibilities are worth exploring as adolescents continue to face growing levels of loneliness and disconnection that have worsened as a result of the Covid‐19 pandemic (Farrell et al, 2023; Twenge et al, 2021). If the Project DREAM intervention proves effective in fostering greater social connection, it will be worth it to explore all possible avenues for widespread implementation.…”
Section: Discussionmentioning
confidence: 99%